(untitled) (Scientific journal of the Fergana State University, 2023)
In recent years, language games have attracted teachers not only by the opportunity to improve the language experience, but also by the fact that they create an environment of free communication. Language games are multimodal and interactive, which leads to the perception, behavior, emotional and cognitive development of students provides the creation of a learning environment. In this article, the author used various language games to study the effectiveness of language games in developing students’ speaking skills in a German lesson. Research has shown that when students are given the opportunity to speak, there are positive changes in their development of speaking skills in the classroom. This article discusses the effectiveness of games in the development of conversational skills in German learners.